IMPROVING STUDENTS’ MOTIVATION THROUGH ENGLISH ONLINE LEARNING SPEAKING SKILLS - Tsabita Ananda Harahap (PROJECT (Professional Journal of English Education), 2021)
This study aims to discuss the efforts that can be made to increase students' motivation to learn English related to speaking skills in online learning during the pandemic. In this study, researchers are expected to provide information related to student motivation in carrying out learning related to speaking skills through online learning and the role of the teacher as a material deliverer who can provide more effective learning speaking material to students. By using the secondary data collection method, researcher uses related previous findings with research being written regarding increasing students' motivation in learning speaking skills during online learning. The specific purpose of this research is to help teachers to be able to find out what factors and media can help increase students' motivation in learning speaking skills. The findings of this study reveal that motivation becomes an important role in the process of students learning speaking skills through online learning, by using the right media students can pay more attention to the material presented. Keywords:  Online Learning, Motivation, Speaking Skills